Vertical Movement of Head, Withers, and Pelvis of High-Level Dressage Horses Trotting in Hand vs. Being Ridden - Hilary M. Clayton; Sarah Jane Hobbs; Marie Rhodin; Elin Hernlund; Mick Peterson; Rosalie Bos; Filipe Serra Bragança (Animals)
Prior to international competitions, dressage horses are evaluated for fitness to compete while trotting in hand on a firm surface. This study compares the kinematics of experienced dressage horses trotting under fitness-to-compete conditions vs. performing collected and extended trot when ridden on a sand-fiber arena surface. The hypotheses are that the vertical range of motion (ROM) and left–right asymmetries in minimal and maximal heights of axial body segments at ridden trot exceed those when trotting in hand. Inertial measurement units (IMUs) attached mid-dorsally to the head, withers, and pelvis of 19 actively competing dressage horses measured the vertical ROM and left–right asymmetries in minimal (MinDiff) and maximal (MaxDiff) heights of the midline sensors. The vertical ROM was greater for both types of ridden trot, reflecting greater impulsion in response to the riders’ aids. Head MinDiff/MaxDiff and withers MaxDiff were significantly higher under both ridden conditions. Pelvis MinDiff was significantly the largest for collected trot. Compared with trot in hand, left–right differences in limb protraction were larger for extended and collected trot in the forelimbs but only for extended trot in the hind limbs. The rider’s influence increases the horse’s impulsion and vertical ROM, which may exacerbate inherent asymmetries in muscular strength when lowering the haunches and elevating the withers.